Silver clouds, dark lining a concise guide to cloud computing - Reed, Archie (Prentice Hall, 2010)
The Executive's Strategic Guide to Driving Maximum Business Value from Cloud Services Cloud services represent a fundamental shift in how individuals, enterprises, and governments conduct business, interact, and use technology. If used effectively, they can increase business agility and focus, simplify capacity planning, and strengthen cost control. Unsurprisingly, however, the cloud also presents risks. In this concise, executive level book, leading experts Archie Reed and Stephen G. Bennett share the insights and guidance decision-makers need to drive maximum value from cloud services--and avoid the pitfalls. The authors explain what cloud computing is, how it works, who provides cloud services, and how companies are using them. Next, they walk through the entire cloud lifecycle, offering expert guidance on planning, governance, compliance, security, operations, administration, management, and more. You'll learn how to: · Assess the opportunities, benefits, and risks of cloud services in your environment · Use the cloud to improve processes, accelerate system/product delivery, or create entirely new products and businesses · Approach the cloud strategically (and learn why you should) · Understand cloud infrastructure, operations, and standards from the decision-maker's point of view · Build on existing solution architecture, design practices, and SOA investments · Ensure appropriate control, monitoring, compliance, and security · Use IT process standardization to simplify cloud services management · Define a flexible roadmap that enables multiple projects to move forward in parallel, and can change as the marketplace evolves Cover illustration by RapidEye /iStockphoto.com.